Forest or oil palm plantation? Interpretation of local responses to the oil palm promises in Kalimantan, Indonesia - Yuliani, L.; Groot, W.T. de; Knippenberg, L.; Bakara, D.O. (Elsevier, 2020)
Global land use/land cover change is dominated by the expansion of cash crops plantations, replacing natural ecosystems including forests. International trade is an important factor in this process. Increasing demand on certain crops has triggered plantation expansion and deforestation, and influence local land use in other countries (land teleconnections). Oil palm expansion is one of the most prominent examples of land teleconnections. In Indonesia, oil palm plantations area increased from 1.1 million ha in 1990 to 11.2 million ha in 2015. According to the Indonesian Law on Plantation, the indigenous people's decisions play important roles in land use decisions. This paper investigates what were the factors (drivers) determining the individual-level responses to the oil palm promises in West Kalimantan. These questions are not only important for the future of Kalimantan’s rainforest but will also enrich deforestation and conservation-development discourses. We selected 49 respondents for interviews and focus groups such that people who opposed and people who supported the conversion were both well represented. Much attention was paid to arrive at a balanced set of operational variables, such as the economic resilience, agency and embeddedness of actors and the degree to which actors had appreciated and believed the oil palm promise. Data were analyzed through the QCA method. The outcomes show a perfect association of appreciation of the oil palm promises, belief in them and the decision to support the oil palm. This was not strongly associated with low economic resilience however; economically less resilient respondents could reject the oil palm conversion, while economically resilient respondents could support it. In other words, the data do not point to a poverty/deforestation nexus. Rather, the data suggest the existence of an ‘embeddedness / rejection nexus’; people that were well-connected to community, traditions and nature held long-term motivations and rejected the oil palm promise, and vice versa. More attention to this phenomenon will help bridge conservation-development objectives in Kalimantan.